Self-Regulated Learning Difference between Male and Female Students - Said Alhadi; Wahyu Nanda Eka Saputra; Agus Supriyanto; Augusto Da Costa; Ediyanto Ediyanto (Universitas Ahmad Dahlan, 2018)
The present study aimed to identify self-regulated learning difference between male and female students in Bantul Regency, Special Region of Yogyakarta, Indonesia. The present study employed quantitative approach with comparative design, the sample of the study was 300 students comprising of 164 male students and 135 female students. The samples were selected using stratified random sampling technique. The instrument that was employed was SRL scale. Independent Samples Test emerged as the data analysis technique to identify SRL difference between male and female students. The result of the study showed that there was significant difference between male and female students' SRL. Based on the SRL average level, female students possess higher level of SRL than male students. The result of the study can be used as initial assessment by school counselor in order to develop a guidance and counseling program concerning SRL.